Potential of Ginger (Zingiber officinale), as anti-hypercholesterolemia to prevent metabolic syndrome: Systematic Literature Review - Melani, Beta; Vikasari, Suci Nar (Universitas Negeri Semarang, 2022)
Abstract Background: One of the symptoms of metabolic syndrome is an increase in cholesterol levels in the blood. Ginger (Zingiber officinale) is a herbal plant that has several active compounds that can help improve lipid levels in the blood. Aim: This systematic study was conducted to examine the potential of ginger as an anti-hypercholesterolemia to prevent metabolic syndrome. Methods: The study was conducted on Indonesian-language articles through the Google Scholar Indonesia database. The inclusion criteria used were articles in Indonesian, preclinical and clinical experimental research, and complete articles that were accessible free of charge. Results: The results of the study show that the anti-cholesterol effect of ginger has been proven both preclinically and clinically. To reduce blood cholesterol levels, ginger can be used combined with other herbs. Some of the active ingredients in ginger are phenolic compounds, including gingerols and shogaols. The suspected mechanism of action is to affect the HMG-CoA reductase enzyme by inhibiting the oxidation pathway and as antiinflammation. Conclusion: Ginger has the potential to prevent metabolic syndrome by reducing cholesterol levels in the blood Keywords: Ginger, Zingiber officinale, hypercholesterolemia, metabolic syndrome